Deviation of Language Politeness Principles in Counter-Comments by Netizens on The Youtube Channel "Tribun Jateng" - Rohman, Ahmad Sani Saefur; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: The purpose of this research is to investigate the use and deviations of linguistic politeness in counter-comments by netizens on videos uploaded by the YouTube channel Tribun Jateng related to the title "Viral Oklin Fia TikToker Uploads Content Licking Ice Cream, Netizens Suspect Blasphemy." Methodology: The research employed a descriptive research method with a qualitative approach. The data source in this study consists of speech descriptions found in counter-comments on the YouTube video of Tribun Jateng titled "Viral Oklin Fia TikToker Uploads Content Licking Ice Cream, Netizens Suspect Blasphemy." Results: Data collection in this research was carried out through note-taking techniques. The results of the research indicate netizen opposition to Oklin Fia, who uploaded inappropriate content that does not align with Islamic norms in terms of dressing and the content on his social media account. Thus, communication can also be understood as a process in which the speaker and the interlocutor mutually understand the conveyed messages. Applications/Originality/Value: From various expert opinions on communication, it can be concluded that communication plays a crucial role in the continuity of human life. Communication is not only conducted through face-to-face interactions but also through indirect means, such as social media.